2005
DOI: 10.4049/jimmunol.174.6.3187
|View full text |Cite
|
Sign up to set email alerts
|

Rationally Engineered Therapeutic Proteins with Reduced Immunogenicity

Abstract: Chronic administration of protein therapeutics may elicit unacceptable immune responses to the specific protein. Our hypothesis is that the immunogenicity of protein drugs can be ascribed to a few immunodominant helper T lymphocyte (HTL) epitopes, and that reducing the MHC binding affinity of these HTL epitopes contained within these proteins can generate drugs with lower immunogenicity. To test this hypothesis, we studied the protein therapeutic erythropoietin (Epo). Two regions within Epo, designated Epo 91–… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
173
2

Year Published

2007
2007
2017
2017

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 160 publications
(180 citation statements)
references
References 44 publications
5
173
2
Order By: Relevance
“…The direct genetic modification used in this study eliminates the additional step of PEGylation and retains the full cytotoxic capability of parental molecule. Other studies have shown that using genetic engineering to mutate T-cell-specific epitopes and the proteolytic cleavage site can improve the pharmacokinetic profile and in vivo efficacy of the biological drug (Tangri et al, 2005;Weldon et al, 2008). Additional studies may show that incorporation of similar mutations into EGF4KDEL 7Mut can further enhance its already potent antitumour activity.…”
Section: Discussionmentioning
confidence: 99%
“…The direct genetic modification used in this study eliminates the additional step of PEGylation and retains the full cytotoxic capability of parental molecule. Other studies have shown that using genetic engineering to mutate T-cell-specific epitopes and the proteolytic cleavage site can improve the pharmacokinetic profile and in vivo efficacy of the biological drug (Tangri et al, 2005;Weldon et al, 2008). Additional studies may show that incorporation of similar mutations into EGF4KDEL 7Mut can further enhance its already potent antitumour activity.…”
Section: Discussionmentioning
confidence: 99%
“…Alternative approaches are to identify and remove B-cell or T-cell epitopes (13)(14)(15)(16)(17). We have recently used a mouse model to identify the major B-cell epitopes in the PE38 portion of RITs made by our group (18).…”
mentioning
confidence: 99%
“…In a study by Tangri et al, rationally designed and engineered erythropoietin, with epitopic regions modulated for HLA affinity, were found to be both bioactive and less immunogenic (78).…”
Section: Current Approaches For Reducing Alloimmunization Against Promentioning
confidence: 99%